Adjacent interdigital pinning: a pilot study of a novel technique for periarticular base fracture of proximal phalanx - Sastravaha, Nattawut; Taweewuthisub, Worasun; Weerasopone, Soarawit (Chulalongkorn Medical Journal, 2023)
Background : Fractures of the phalanx account for more than 20% of all upper extremities fracture, mostly, proximal phalanx (P1) fracture. Managing periarticular fracture of P1 has remained a challenging problem for hand surgeon especially comminuted fracture. Several operative techniques were performed to gain anatomical reduction, stable fixation and early range of motion. We proposed a novel technique: adjacent interdigital pinning. Objective : The aims of this study were determined the outcome of periarticular base of P1 fractures performed by the surgical procrdure, namely: adjacent interdigital pinning technique. Methods : A periarticular base of P1 fracture was reduced by distal traction. The early joint exercise was allowed because both metacarpophalangeal (MCP) and proximal interphalangeal (PIP) remained free of motion. The two or three pins were inserted into the proximal phalanx of injured digit to the proximal phalanx of nearby digit after the fracture was reduced. Fluoroscopy was used to check alignment and reduction. Range of motion (ROM) exercise strated immediately after the operation. Results : Three patients with periarticular P1 fractures were recruited. The average follow-up period was 3 months. The mean ROM of the injured MCP of those 3 patients was 83o. The mean ROM of PIP was 80o. The patients reported visual analogue pain score of 0 - 1 after 3 months of operation. The grip strength was at least 80% compared to uninjured side. All cases were union within 4 weeks without serious complication. The angulation of fracture sites were not more than 10 degree in coronal and sagittal view. Conclusion : Adjacent interdigital pinning is economical, easy for application and provides good results; thus, it should be an alternative way to manage periarticular P1 fracture.